The Influence of Motivation and Supervision on Work Discipline of Afdeling III PT Employees. Tasma Puja Kebun Sei. Kuamang, Kampar Regency - Syarah, Desti; Suryalena, Suryalena (CV. Rayyan Dwi Bharata, 2024)
This research aims to analyze the influence of motivation and supervision on the work discipline of PT Division III employees. Tasma Puja Kebun Sei Kuamang Kampar Regency. The research method used is quantitative. The sample for this research was 91 respondents, with data collection techniques using questionnaires. The data obtained was analyzed through linear regression analysis with the SPSS program. The research results show; (1) There is an influence of motivation on the work discipline of Afeling III PT employees. Tasma Puja Kebu Sei Kuamang Kampar Regency. The calculated t value t table or 9.677 t table 1986 was obtained and the significance was 0.000 0.05. The results of simple linear regression analysis show that if motivation increases by 0.535, it will increase the work discipline of PT Division III employees. Tasma Puja Kebun Sei Kuamang Kampar Regency is 5,830 consistently. (2) There is an influence of supervision on the work discipline of Afdeling III PT employees. Tasma Puja Kebun Sei Kuamang Kampar Regency. The calculated t value t table or 9.474 t table 1986 was obtained and the significance was 0.000 0.05. The results of a simple regression analysis show that if supervision increases by 0.721 it will increase the work discipline of PT Division III employees. Tasma Puja Kebun Sei Kuamang Kampar Regency is 4,662 consistently. (3) There is an influence of motivation and supervision on the work discipline of Afdeling III PT employees. Tasma Puja Kebun Sei Kuamang Kampar Regency. From the results of the F test, the calculated f value f table is 56.675, which is greater than f table 3.10 and sig 0.000 0.05. The results of the coefficient of determination test show that motivation and supervision contribute to the work discipline of PT Afdeling III employees. Tasma Puja Kebun Sei Kuamang Kampar Regency was 56.3% while the remaining 43.7% was influenced by other variables not studied.